Recovery, self-stigma, quality of life, and the determinants among people with schizophrenia: a systematic review - Sawab, Sawab; Yusuf, Ah; Fitryasari, Rizki; Iswanti, Dwi Indah (Intelektual Pustaka Media Utama, 2025)
Recovery and quality of life for people with schizophrenia (PWS) are persisting challenges in mental health services. Therefore, this research aims to investigate factors contributing significantly to PWS recovery for quality-of-life enhancement. A comprehensive search across six databases, including Scopus, ScienceDirect, ProQuest, SpringerLink, Web of Science, and CINAHL generated 196, 122, 134, 79, 51, and 113 articles, respectively, for screening. These 695 articles focused on patients diagnosed with schizophrenia in recovery, as well as comprised journal publications from 2019 to 2023 and quantitative or qualitative research published in English. A total of 22 articles that met the inclusion criteria were subject to a review process. The results showed that PWS recovery was influenced by coping strategies, illness severity, treatment compliance, hope, spirituality, social support, and partnerships, while self-stigma hindered recovery and quality of life. However, spirituality was found to significantly foster hope, self-confidence, self-control, and meaning for PWS. Health profesional played an important role in the recovery process through the establishment of partnerships, provision of coping skills, and empowerment of patients.